The obligation of double record of the plea agreement and the access by technical defense - Luiz Antonio Borri; Rafael Junior Soares (Revista Brasileira de Direito Processual Penal)
This article aims to discuss the relevant subject of double record of plea agreement, as well as the possibility of withholding access to one of the registration forms from the investigated/accused person. The matter is highlighted notably in face of the article writing 4, §13, of Law 12.850 / 13, which provides that, whenever possible, should promote the registration record by audiovisual means, indicating expressly of registration of the statements collected in collaboration. In addition, current data indicate the existence of a significant number of new technologies, endowed with skillful mechanisms to promote the registration of declarations by the means provided by law, indicating that the legal authorities have the onus to justify the reasons that lead to the unavailability of audiovisual record of the award-winning collaborator testimony. Finally, it is salutary to make available to defense all forms of registration of the declarations obtained in the case of delation, mainly because the Public Prosecutor's Office has knowledge of such elements, so that the restriction of access implies violation of parity of arms.